Musical journey: a virtual world gamification experience for music learning - Gomes, José (2014)
Games are an integral part of the learning process of humans, in particular for children, who exploit the imagery as an intrinsic part of their lives. Features from games have been successfully implemented as a means to captivate and motivate students to perform learning at various levels of education in traditional schools. This paper presents a virtual world – Musical Journey – representing the Aesthetic Periods of Music History. This virtual environment allows students to freely explore and discover the most relevant sounds, musical instruments and composers, ranging from the first century to present time. Musical Journey is a three-dimensional space that simulates an area similar to a museum or art gallery. In that context, musical contents are grouped into thematic exhibition halls, where users can interact with the exhibition. Musical Journey was developed with the Vivaty Studio program, exported to the standard X3D and configured for local or remote access using X3DOM enrolled in HTML5 pages, displaying 3-D contents in a web browser without any plug-ins. In this paper, we explain how the introduction of the concept gamification, through a process whereby we insert elements of game mechanics and design in the virtual world, contributed to the learning and motivation of the study of these curricula. We conclude this paper by presenting a case-study conducted among a sample group of students from the 2nd Cycle of Basic Education contemplating the use of this Virtual world in an educational context.